Tricking Arthrinium malaysianum into Producing Industrially Important Enzymes Under 2-Deoxy D-Glucose Treatment - Mukherjee, Soumya; Chandrababunaidu, Mathu Malar; Panda, Arijit; Khowala, Suman; Tripathy, Sucheta (Frontiers in Microbiology, 2016)
This study catalogues production of industrially important enzymes and changes in transcript expression caused by 2-deoxy D-glucose (2-DG) treatment in Arthrinium malaysianum cultures. Carbon Catabolite Repression (CCR) induced by 2-DG in this species is cAMP independent unlike many other organisms. Higher levels of secreted endoglucanase (EG), β-glucosidase (BGL), β-xylosidase (BXL) and filter paper activity assay (FPase) enzymes under 2-DG treatment can be exploited for commercial purposes. An integrated RNA sequencing and quantitative proteomic analysis was performed to investigate the cellular response to 2-DG in A. malaysianum. Analysis of RNASeq data under 2-DG treated and control condition reveals that 56% of the unigenes do not have any known similarity to proteins in non redundant database. Gene Ontology IDs were assigned to 36% of the transcripts (13260) and about 5207 (14%) were mapped to Kyoto Encyclopedia of Genes and Genomes pathway (KEGG). About 1711 genes encoding 2691 transcripts were differentially expressed in treated vs. control samples. Out of the 2691 differentially expressed transcripts, only 582 have any known function. The most up regulated genes belonged to Pentose Phosphate Pathways and carbohydrate degradation class as expected. In addition, genes involved in protein folding, binding, catalytic activity, DNA repair, and secondary metabolites were up-regulated under 2-DG treatment. Whereas genes encoding glycosylation pathways, growth, nutrient reservoir activity was repressed. Gene ontology analysis of the differentially expressed genes indicates metabolic process (35%) is the pre-dominant class followed by carbohydrate degradation (11%), protein folding and trafficking (6.2%) and transport (5.3%) classes. Unlike other organisms, conventional unfolded protein response (UPR) was not activated in either control or treated conditions. Major enzymes secreted by A. malaysianum are those degrading plant polysaccharides, the most dominant ones being β-glucosidase, as demonstrated by the 2D gel analysis. A set of 7 differentially expressed mRNAs were validated by qPCR. Transmission electron microscopy analyses demonstrated that the 2-DG treated cell walls of hyphae showed significant differences in the cell-wall thickness. Overall 2-DG treatment in A. malaysianum induced secretion of large amount of commercially viable enzymes compared to other known species.